CAMPAIGN TEAM AND MEDIA AGENDA IN THE NEWS OF SIMULTANEOUS REGIONAL ELECTIONS DURING THE PANDEMIC IN 2020 - Bahanan, Umar Fauzi (Universitas Nasional, 2020)
The campaign team's agenda tends to ignore health protocols as it intends to win the election. At the same time, some media agendas are in line with the campaign team's plan; some are not in line with the agenda of the campaign team. If the media's agenda is in line with the campaign team, it can be said that the media is a partisan media, which is not in line with media that strives to be independent. With the Agenda Setting Media Theory, the analysis is done by observing and studying literature. It is concluded that the campaign team agenda tends to ignore health protocols, with the orientation of winning the 2020 regional elections in the pandemic era, while the media agenda tends to see violations of health protocols committed by the campaign team as things that have news value to be reported continuously as self-satisfaction, whether to make the campaign team deterred, embarrassed, or even annoyed by the news about the health protocol violation by the campaign team in holding regional head elections in the 2020 pandemic era